Comparison of type of set and set zone between China and Italy during the 2023 FIVB U21 Women’s Volleyball Championships / Anis Shafira Abdul Harith ... [et al.]. - Abdul Harith, Anis Shafira; Esa, Muhammad Nabil; Ismail, Arisya; Mohamed, Muhamad Noor; Md Radzi, Noor Azila Azreen; Syed Mud Puad, Sharifah Maimunah (2024)
The 2023 FIVB Volleyball Women’s U21 World Championship, held in Mexico from 17 to 26 August, marked the 22nd edition of the tournament, featuring national teams under the age of 20. This study focuses on the top two countries, China and Italy, analyzing their setting zones during the championships. Two types of sets, standing and jumping, were examined across six setting zones: zones 1, zone 2, zone 3, zone 4, zone 5 and zone 6. A total of 15 matches played by China (N = 770) and Italy (N = 709) were analyzed using Microsoft Excel and Statistical Package for the Social Sciences (SPSS) version 26.0. Reliability and validity testing via Pearson Correlation revealed r = 0.93, while descriptive statistics indicated that Italy exhibited higher means and larger standard deviations for both the type of set and setting zone variables, suggesting greater variability compared to China. Chi-square tests of independence showed significant associations between the type of set and setting zones for both China (χ² = 84.120, df = 5, p = 0.001) and Italy (χ² = 66.829, df = 5, p = 0.001), indicating distinct strategic preferences in their set plays. The analysis revealed that the jumping set directed to zone 4 is the most effective combination. China and Italy, the top two teams, exhibited a significant preference for this zone, with the highest frequencies of sets directed towards Zone 4. This strategic insight highlights the importance of targeting Zone 4 to optimize set plays and enhance competitive performance in volleyball. The study underscores the importance of strategic planning in volleyball demonstrating that both countries employ unique approaches to optimize performance and counter opponents’ strategies effectively.